2016
DOI: 10.2147/ott.s105787
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglycerate dehydrogenase is a novel predictor for poor prognosis in gastric cancer

Abstract: Purpose Phosphoglycerate dehydrogenase (PHGDH) acts as a key metabolic enzyme in the rate-limiting step in serine biosynthesis and plays an important role in metastasis of several cancers. The aim of this study was to investigate the prognostic value of PHGDH in gastric cancer (GC). Methods The messenger RNA expression of PHGDH was determined in 20 pairs of cancerous and adjacent nontumor tissues by real-time polymerase chain reaction. Immunohistochemistry of PHGDH was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 35 publications
(48 reference statements)
0
8
0
Order By: Relevance
“…The lack of serine in the TME caused by the upregulation of PHGDH can impair the function of immune T cells. The expression of PHGDH was negatively correlated with the 5-year survival rate of GC patients, and multivariate analysis shows that it was an independent prognostic factor for the prognosis of GC ( Xian et al, 2016 ). However, the effect of high expression of PHGDH on the GC TME and immune cells has not yet been studied.…”
Section: Discussionmentioning
confidence: 97%
“…The lack of serine in the TME caused by the upregulation of PHGDH can impair the function of immune T cells. The expression of PHGDH was negatively correlated with the 5-year survival rate of GC patients, and multivariate analysis shows that it was an independent prognostic factor for the prognosis of GC ( Xian et al, 2016 ). However, the effect of high expression of PHGDH on the GC TME and immune cells has not yet been studied.…”
Section: Discussionmentioning
confidence: 97%
“…various types of cancer (eg, breast, 29 bladder, 30 glioma, 31 cervical, 32 melanoma, 33 non-small-cell lung, 34 colorectal 11 and gastric 35 ), dysregulating serine metabolism and contributing to tumor progression. Inhibition of PHGDH activity by si-RNA or inhibitors can disrupt the serine synthesis pathway and restrain the growth and proliferation of tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…The product is then subsequently converted into phosphoserine via transamination by phosphoserine aminotransferase (PSAT1) and, ultimately, to serine via phosphate ester hydrolysis and the enzyme PSPH, serine is also an activator of PKM2 in the glycolysis. Over recent years, an increasing number of studies have focused upon PHGDH in cancer research, which is found to exhibit elevation and controlled flux throughout the serine biosynthetic pathway in cancer cells [ 21 ]. Interestingly, The overexpression of PHGDH is often associated with progression of cancers, and the inhibitors of PHGDH reduce the glycolysis and suppress the growth of cancers [ 22 ].…”
Section: Discussionmentioning
confidence: 99%